Subjective Cognitive and Communicative Complaints and Health-Related Quality of Life in Parkinson's Disease with and without Mild Cognitive Impairment (2023)
Introduction: Mild Cognitive Impairment (MCI) is common in Parkinson's Disease (PD). Few studies have compared the Health-Related Quality of Life (HRQoL) in patients with and without MCI due to PD (PD-MCI), and its correlation to patients’ subjective cognitive and communicative difficulties has not been explored. Objective: We aimed to compare HRQoL in PD-MCI and PD without MCI (PD-nMCI), and explore its possible relationship to subjective cognitive and communicative complaints. Methods: We included 29 PD-nMCI and 11 PD-MCI patients. The HRQoL was assessed with the Parkinson's Disease Questionnaire-39 (PDQ-39): its Cognition dimension was used as a measure of subjective cognitive complaints, its Communication dimension for subjective communicative complaints, and the summary index (PDQ-39 SI) as an indicator of HRQoL. Non-parametric partial correlations between the Cognition and Communication dimensions, and the adjusted PDQ-39 SI were conducted. Results: PD-MCI patients had greater subjective cognitive and communicative complaints and worse HRQoL than PD-nMCI patients. In the PD-MCI group, both subjective cognitive and communicative complaints exhibited significant direct correlations with the adjusted HRQoL scores. Conclusions: HRQoL seems to be affected in PD-MCI, and it might be influenced by greater subjective cognitive and communicative complaints. Including patient-reported outcome measures of HRQoL, and providing cognitive and speech rehabilitation, as well as psychotherapeutic strategies to face these deficits can enhance the patient-centred approach in PD.